2014
DOI: 10.1113/jphysiol.2013.266221
|View full text |Cite
|
Sign up to set email alerts
|

Carotid body denervation improves autonomic and cardiac function and attenuates disordered breathing in congestive heart failure

Abstract: Key pointsr A strong correlation between disordered breathing patterns, elevated sympathetic nerve activity and enhanced chemoreflex sensitivity exists in patients with heart failure.r Evidence indicates that disordered breathing patterns and increased sympathetic nerve activity increases arrhythmia incidence in patients with heart failure.r Enhanced coupling between sympathetic and respiratory neural drive underlies elevated sympathetic nerve activity in an animal model of sleep apnoea.r We investigated the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
220
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(230 citation statements)
references
References 59 publications
8
220
1
1
Order By: Relevance
“…The apneas have been tentatively attributed to recurrent episodes of CNS hypocarbia that silence CRCs (Dempsey et al, 2012;Marcus et al, 2014). This interpretation agrees with the finding that respiratory alkalosis silences RTN in conscious rats (Basting et al, 2015).…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…The apneas have been tentatively attributed to recurrent episodes of CNS hypocarbia that silence CRCs (Dempsey et al, 2012;Marcus et al, 2014). This interpretation agrees with the finding that respiratory alkalosis silences RTN in conscious rats (Basting et al, 2015).…”
Section: Introductionsupporting
confidence: 84%
“…In CCHS patients, breathing is much better maintained during REM than non-REM sleep (Fleming et al, 1980). In short, reduced CRC activity resulting from carotid body hyperactivity (hypoxia, CHF) (Marcus et al, 2014) or RTN lesion (putative cause of CCHS) appears to cause central sleep apnea (CSA) selectively during non-REM sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic CO 2 therapy, applied during the hyperventilation phase of CSR to prevent hypocapnia, can resolve CSR during wakefulness without considerably raising mean ventilation (131,132). Finally, denervation of the carotid-body chemoreceptors has been shown in animal studies to improve survival in CHF, and a case patient with CHF improved sleep disordered breathing, exercise capacity and quality of life (133,134).…”
Section: Novel and Future Therapiesmentioning
confidence: 99%
“…Ribeiro et al (2013) demonstrate how CBD prevents the development of insulin resistance and hypertension induced by hypercaloric diets. The most comprehensive animal study with which we are familiar is that of Marcus and his colleagues in CHF rabbits (Marcus et al, 2014). In brief, their study showed how CBD reduced sympathetic nerve activity, disordered breathing patterns, arrhythmia incidence, and sympatho-respiratory coupling in CHF rabbits.…”
Section: Treatment Of the Target To Reduce Its Impactmentioning
confidence: 99%